Acceptance & commitment therapy for school leaders' well-being: an initial feasibility study. Issue 1 (2nd January 2021) - Gillard, Duncan; Wright, David; McNally, Aoife; Flaxman, Paul E.; McIntosh, Ross; Honey, Kyla
ABSTRACT: Acceptance and Commitment Therapy (ACT) has evolved a considerable evidence-base in recent years. One area wherein the model has demonstrated strong empirical support is through its application within the workplace. However, little empirical work has been carried out within the educational workforce and even less has been done with school leaders specifically. This paper reports on an initial feasibility study, using a group-based ACT programme to promote the well-being of school leaders. Seven leaders attended the programme, and completed established measures of well-being, burnout and valued living before and after the programme. The patterns of change indicated improvements on all three measures from pre- to post-intervention. Transcripts from semi-structured interviews were thematically analysed, revealing three themes: Increasing Awareness; Building Resilience; and a Safe and Supportive Group. Results and analyses are discussed in terms of future directions for the field and in terms of potential implications for the current COVID-19 pandemic.